Kemampuan membaca dan menghafal Alquran santri melalui penguasaan kitab Tuhfatul Athfal - Arfandi, Muhammad Siddik; Nasution, Wahyuddin Nur; Halimah, Siti (Ta'dibuna: Jurnal Pendidikan Islam, 2023)
This study contains the ability to read and memorize the Qur'an of students through the Book of Tuhfatul Athfal. This research is a qualitative analytic type. Data collection through observation, interviews, documentation, and tests. The data that has been collected is analyzed by data reduction, presentation, and drawing conclusions. In the process of testing the validity of the data, research writing used extended observations, triangulation, and member checks to draw conclusions and obtain valid data about students' ability to read and memorize the Qur'an through the book Tuhfatul Athfal. Based on the results of the data analysis, the student's ability to read and memorize the Qur'an through the book Tuhfatul Athfal is quite good. This is evidenced by the results of tests on the students' tajwid comprehension and memorization of the Qur'an which include; tests for the accuracy of makhorijul letters, shifatul letters, ahkamul letters, mad wal qoshr, and fluency in memorizing the Qur'an. The test results stated that the students at the Banii Adama Tahfidz Alquran House were able to recite the Alquran recitation according to predetermined rules and were able to memorize the Alquran fluently and fluently. Abstrak Penelitian ini berisi tentang kemampuan membaca dan menghafal Alquran santri melalui Kitab Tuhfatul Athfal. Penelitian ini berjenis kualitatif analitik. Pengumpulan data melalui observasi, wawancara, dokumentasi dan tes. Data yang sudah dikumpul dianalisis dengan reduksi data, penyajian data dan penarikan kesimpulan. Dalam proses uji keabsahan data, penulisan penelitian menggunakan perpanjangan pengamatan, triangulasi, dan member check untuk menarik sebuah kesimpulan dan mendapatkan data yang valid tentang kemampuan membaca dan menghafal Alquran santri melalui kitab Tuhfatul Athfal. Berdasarkan hasil analisis data bahwa kemampuan membaca dan menghafal Alquran santri melalui kitab Tuhfatul Athfal sudah cukup baik. Ini dibuktikan dengan hasil tes pemahaman tajwid dan hafalan Alquran santri yang meliputi; tes ketepatan makhorijul huruf, shifatul huruf, ahkamul huruf, mad wal qoshr, dan kelancaran hafalan Alquran. Hasil tes menyatakan bahwa santri di Rumah Tahfidz Al-Qur’an Banii Adama mampu melafazkan bacaan Alquran sesuai kaidah yang telah ditetapkan dan mampu menghafalkan Alquran dengan lancar dan fasih.